Numerical investigation of conjugate mixed convection in a rectangular cavity with heat-conducting walls of finite thickness under conditions of radiant energy supply; Heat Transfer Research; Vol. 48, iss. 16 - Kuznetsov G. V. Geny Vladimirovich (2017, 2017)
Title screen